Electrically controllable router of interlayer excitons - Liu, Yuanda (2020)
Optoelectronic devices that allow rerouting, modulation, and detection of the optical signals would be extremely beneficial for telecommunication technology. One of the most promising platforms for these devices is excitonic devices, as they offer very efficient coupling to light. Of especial importance are those based on indirect excitons because of their long lifetime. Here, we demonstrate excitonic transistor and router based on bilayer WSe2. Because of their strong dipole moment, excitons in bilayer WSe2 can be controlled by transverse electric field. At the same time, unlike indirect excitons in artificially stacked heterostructures based on transition metal dichalcogenides, naturally stacked bilayers are much simpler in fabrication.